Highlights and Implication of A Deep-Crustal Seismic Reflection Survey in the Arafura Sea Region - Granath, James W.; Dinkelman, Menno G.; Christ-Stringer, Janice C.; Emmet, Peter A. (Ikatan Ahli Geologi Indonesia, 2012)
A regional 2-D reconnaissance seismic survey, ArafuraSPAN™, provideS pre-stack depth images down to 40 km, allowing new interpretations of the basement structure and its influence on the overlying sedimentary cover of at least seven geological provinces. In the Arafura Sea, the new data have revealed an enormous two-part Proterozoic supracrustal section comprised of a some 15+ km thick Arafura Basin and an underlying additional 15+ km McArthur Basin equivalents. The stratigraphic thicknesses of these rocks make up virtually the entire crust under the Arafura platform. Stratiform reflections are interpretable to a depth of over 30 km, an imaging first and a game changer in terms of understanding the regional geological framework. The best available interpretation of this section is that it represents a peri-cratonic large igneous province of Proterozoic age, preserved as virtually the entire crust. In the Banda Sea, structural relationships between the Tanimbar accretionary prism, the Weber Deep, and the platform suggest that the Weber Deep initiated as a forearc extensional event the severed the accretionary prism from its hard volcanic core, and then evolved into a major basin within the Banda Basin. The Seram thrust belt is shown to lie above a strike-slip system that separates the Banda microplate from the Bird's Head, and forms the plate boundary in that area.